Effectiveness of the Training Program Based on Experiential Learning Approach to Enhance the Spirituality of Teachers of The College of Dramatic Arts Students Bunditpatanasilpa Institute - Ragumpol, Nutta (Journal of Behavioral Science for Development, 2023)
This study aimed to study effectiveness of enhance the spirituality of teachers development program. It is a quasi-experimental research. The sample were the first-year students in the field of Dramatic Studies and Music Education (4-year program), College of Dramatic Arts, Bunditpatanasilpa Institute.Forty students were grouped equally into experimental and control groups: 20 students per group. Data were collected using the spirituality of teachers test in a pre-test prior to participating, a post-test immediately after and a follow-up test one month later. The results showed that a post-test period of students received program had of enhance the spirituality of teachers higher than pre-test and control group with statistical significance, in follow-up period of 1 month, the students who received program had of the spirituality of teachers decreased little from post - test, still higher than the students who did not receive the spiritual teacher program.At the result, this research showed that using the spirituality of teachers program, It is effective for enhance the spirituality of teachers of students. Therefore, the use of the study model should be encouraged to enhance in the long term. to maintain the spirit of being a teacher to remain permanently.